(untitled) (Research, Society and Development, 2020)
Bacuri pulp oil (Attalea phalerata Mart. Ex Spreng) has medicinal properties due to a high concentration of carotenoids and palmitoleic acid from the Omega-7 group that can benefit the health and well-being of fish. The objective was to evaluate the benefits of including bacuri oil in the development and coloring of Mato Grosso (Hyphessobrycon eques Steindachner, 1882). 51 specimens of coarse forest were used, distributed in four units of 10L in individual recirculation system and thermostated water at 28 ° C. During the 60-day trial the fish were fed with commercial diets (DC) and commercial diet plus essential oil of bacuri (5g.kg-1) (DB). At the end of the experimental period, survival, growth, color and thermogenicity were evaluated. The data were analyzed using the Duncan test (P> 0.05). The use of bacuri oil provided a low growth rate, however it is noteworthy that it was longer in relation to the DC group. Consumption was not affected by the addition of bacuri oil, having no effect on the palatability of the diet. However, the trial survival was 73% for DB and 88% for DC. There was no change in the color and thermogenicity of the fish with the inclusion of bacuri oil. The condition factor of DB fish was superior to DC, which demonstrates the ability to promote fish welfare. It was concluded that in the dose used, bacuri essential oil is not recommended for thick bush as a supplement to improve color.